Address public safety challenges of international students on campus. Issue 11 (15th February 2019) - Hope, Joan
Abstract : International students present unique challenges for campus public safety units. In a webinar for the International Association of Campus Law Enforcement Administrators, Ed Book, chief of police, behavioral intervention team chair, and emergency manager at Santa Fe College in Florida; and Angelica Suarez, international student services coordinator at Santa Fe, explained the strategies they use to support these students and meet their needs.